1996
DOI: 10.1128/jvi.70.6.3407-3415.1996
|View full text |Cite
|
Sign up to set email alerts
|

Folding, assembly, and intracellular trafficking of the human immunodeficiency virus type 1 envelope glycoprotein analyzed with monoclonal antibodies recognizing maturational intermediates

Abstract: Monoclonal antibodies (MAbs) that bind linear or conformational epitopes on monomeric or oligomeric human immunodeficiency virus type 1 (HIV-1) envelope glycoproteins were screened for their recognition of maturational intermediates. On the basis of reactivities with gp160 at different times after pulse-labeling, the MAbs were sorted into groups that exhibited binding which was immediate and constant, immediate but transient, delayed, late, or very late. This grouping was consistent with the selectivity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…Env is synthesized on ribosomes associated with the endoplasmic reticulum as a precursor protein, gp160 [5]. Trimerization of gp160 is required for exit from the ER [6]. During transit through the Golgi, gp160 becomes heavily glycosylated and the precursor subunits are cleaved by furin-like proteases to create gp41 (TM) and gp120 (SU) subunits.…”
Section: Introductionmentioning
confidence: 99%
“…Env is synthesized on ribosomes associated with the endoplasmic reticulum as a precursor protein, gp160 [5]. Trimerization of gp160 is required for exit from the ER [6]. During transit through the Golgi, gp160 becomes heavily glycosylated and the precursor subunits are cleaved by furin-like proteases to create gp41 (TM) and gp120 (SU) subunits.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have found that heat shock proteins (HSPs) interact with viral particles. For instance, Hsp70 is associated with vesicular stomatitis [20], the vaccinia virus [21], adenovirus [22], and the gp160 glycoprotein of HIV (during its transportation and oligomerization) [23]. Nef interacts with Hsp40, resulting in an increase in Hsp40 translocation into the nucleus of the infected cells.…”
Section: Introductionmentioning
confidence: 99%
“…Env mRNA is synthesized in the nucleus, and exported with the help of the viral Rev protein to the cytoplasm where it is translated as a gp160 precursor. Gp160 is then translocated through the rough endoplasmic reticulum (ER) (Dettenhofer and Yu, 2001), and folded with the assistance of the chaperone proteins, calreticulin, and calnexin (Otteken et al, 1996). Glycans are added in the Golgi, and subsequently trimmed (Dash et al, 1994;Fenouillet and Jones, 1995).…”
Section: Introductionmentioning
confidence: 99%